2006
DOI: 10.1002/smr.333
|View full text |Cite
|
Sign up to set email alerts
|

Unifying clones with a generative programming technique: a case study

Abstract: Software clones-similar program structures repeated in variant forms-increase the risk of update anomalies, blow up the program size and complexity, possibly contributing to high maintenance costs. Yet, programs are often polluted by clones. In this paper, we present a case study of cloning in the Java Buffer library, JDK 1.5. We found that at least 68% of the code in the Buffer library was contained in cloned classes or class methods. Close analysis of program situations that led to cloning revealed difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Although clones were initially considered undesirable [27], multiple authors later argued that this assumption is not necessarily true and reported corresponding empirical data. Kapser and Godfrey [28] describe several observed patterns of cloning and provide evidence that cloning is used as a principled engineering technique.…”
Section: Related Workmentioning
confidence: 99%
“…Although clones were initially considered undesirable [27], multiple authors later argued that this assumption is not necessarily true and reported corresponding empirical data. Kapser and Godfrey [28] describe several observed patterns of cloning and provide evidence that cloning is used as a principled engineering technique.…”
Section: Related Workmentioning
confidence: 99%
“…Generics could unify 15 among 74 classes under study, reducing the code size by 27%. The solution with generics was subject to certain restrictions that we discussed in [17].…”
Section: Java Buffer Library and Stlmentioning
confidence: 99%
“…The number of modifications to implement Complex buffer in a mixed-strategy representation was 11, as compared to 91 modifications required for the same purpose in the original Buffer library. Further details of this study are described in [17].…”
Section: Java Buffer Library and Stlmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of design patterns is another option to avoid clones by better design [11,12] although this approach can hardly be automated. Likewise, one can develop code generators for highly repetitive code [39].…”
Section: Correctionmentioning
confidence: 99%